(untitled) (Research, Society and Development, 2021)
Therapeutic ultrasound (UST) has been used by physiotherapists since 1950 in the treatment of musculoskeletal injuries. Its actions are mainly associated with increased cell metabolism and promotion of angiogenesis. In muscle, ultrasound is widely used in cases of injury, but little is known about the mechanisms in which it acts, although analgesy, regeneration and muscle strength rehabilitation have already been proven. Thus, this integrative review aimed to list the mechanisms by which the UST acts on muscle regeneration. Twenty-seven studies were selected, all of which were carried out with rodents. In injured muscles, UST seems to activate the phosphorylation pathway of kinases 1 and 2 regulated by extracellular signaling (ERK1/2) and mitogen-activated protein kinase 38 (MAPK p38), reducing the inflammatory response and increasing the expression of myogenic factors. These factors activate the differentiation of muscle satellite cells. The proliferation of muscle cells translates into a greater number of myofibrils, that is, a greater number of contractile units. Thus, the UST can help in muscle rehabilitation, by promoting responses in cell metabolism and favoring the differentiation of satellite cells, with subsequent formation of new fibers.